Effects of empowerment education on the self-management and self-efficacy of liver transplant patients: a randomized controlled trial - Limin Guo; Lezhi Li; Yanfang Lu; Ting Li; Linjun Chen; Liya Jiang; Shihan Zhang; Meijiao Yuan (BMC, 2023)
Abstract Background Despite the increasing survival rates, liver transplant patients experience numerous postoperative complications and encounter significant challenges in long-term self-management. This study aims to examine the effectiveness of empowerment education in enhancing self-management skills and self-efficacy among liver transplant recipients. Methods A randomized, single-blind, single-center trial was conducted in China between August 2019 and September 2020, involving liver transplant recipients. The intervention group received 12 weeks of empowerment education, while the control group received 12 weeks of routine education. .The study assessed the patients' self-management and self-efficacy using the Liver Transplant Recipient Self-Management Questionnaire and the Self-efficacy for Managing Chronic Disease 6-Item Scale. Follow-up assessments were conducted at 1, 3, and 6 months after the intervention. Results Eighty-four patients were initially randomized to either the intervention group (n1 = 42) or the routine education group (n2 = 42). Twelve patients were excluded from the analysis due to loss of follow-up or discontinuation of the intervention, leaving 72 patients (n1 = 35, n2 = 37) for the final analysis. The scores for exercise and lifestyle management were significantly higher in the intervention group than in the control group at 1, 3, and 6 months after the intervention (t = 3.047, 5.875, 8.356, and t = 5.759, 4.681, 11.759, respectively; P < 0.05). At 3 and 6 months after the intervention, the scores for cognitive symptom management, communication with physicians, and self-efficacy were significantly higher in the intervention group than in the control group (t = 5.609, 6.416, and t = 5.576, 11.601, and t = 6.867, 15.071, respectively; P < 0.001). Within the intervention group, self-management scores increased significantly over time, while within the control group, the scores for communication with physicians, lifestyle, and self-efficacy showed a significant decline from 3 to 6 months after routine health education. Conclusions The results of this study suggest that empowerment education is an effective means of improving the self-management and self-efficacy of liver transplant patients, with better outcomes compared to routine health education. These findings have important implications for nursing practice and provide valuable guidance for clinical education of liver transplant patients. Trial registration ChiCTR2200061561.